"I've never been able to burp": Preliminary description of retrograde cricopharyngeal dysfunction in children. (October 2022) - Hoffman, Matthew R.; Schiffer, Breanne; Patel, Raza A.; Smith, Marshall E.
Abstract: Objective: Retrograde cricopharyngeal dysfunction was recently described by Bastian in 2019 and is characterized by an inability to belch, abdominal or chest pressure, odd gurgling noises, and occasional difficulty vomiting. Symptoms tend to worsen with carbonated beverages. Currently, the recommended treatment is cricopharyngeus muscle botulinum toxin injections. Prior studies have included few pediatric patients within larger datasets comprised primarily of adults. We describe our preliminary experience in pediatric patients, including presenting symptoms, treatment approach, and post-treatment outcomes. Methods: Retrospective chart review of pediatric patients (aged <18 years) diagnosed with retrograde cricopharyngeal dysfunction based on clinical history by the senior author. Medical records were reviewed for presenting symptoms, prior testing and treatment, details of treatment, and postoperative outcomes. Results: Five patients with average age of 14 ± 4 (3 females, 2 males) were included. Presenting symptoms included lifelong or nearly lifelong inability to burp (n = 5), bloating (n = 5), awkward gurgling noises (n = 3), and worsening of symptoms with carbonated beverages (n = 5). Two patients had prior normal upper endoscopy. All patients underwent cricopharyngeal botulinum toxin injection under general anesthesia, with 25–50 units of botulinum toxin injected to the posterior cricopharyngeus across 4–5 locations. All patients had resolution of symptoms with follow-up of 1.5–10 months. Conclusions: Retrograde cricopharyngeal dysfunction may be underdiagnosed due to lack of awareness of the condition. Now that the phenomenon of inability to belch has a name and is being reported in the literature, we will likely see more adult and pediatric patients with these symptoms. Pediatric patients may respond similarly to adults. Larger studies with longer-term follow-up and targeted patient-reported outcome measures are needed to characterize disease presentation and treatment outcomes.